Pertanggungjawaban Pidana terhadap Pelaku Tindak Pidana Kepemilikan Serbuk Ampo sebagai Bahan Peledak (Studi Putusan Nomor: 488/Pid.Sus/2021/PN Tjk) - M. Fadel Robby Syahputra; Zulfi Diane Zaini; Angga Alfiyan (Fakultas Hukum, Universitas Jambi, 2022)
One of the cases regarding possession of explosives is in Decision Number: 488/Pid.Sus/2021/PN Tjk which states that the defendant Kurniawan Azhar Amran Bin M. Rosyid is guilty of having been legally and convincingly proven to have committed the crime of possessing, carrying, and possessing supplies to him. or has in his possession, keeps, transports, hides, uses explosives. The research method uses a normative and empirical juridical approach. The results showed that the factors causing the perpetrators to commit the crime of possessing ampo powder as explosives based on Decision Number: 488/Pid.Sus/2021/PN Tjk were factors for self-defense or self-defense. In addition, ampo powder as an explosive resulting from this crime is very popular because ampo powder as an explosive is not registered so it is difficult to track it, moreover it is easy to use by various parties in the territory of Indonesia, including there are people who misuse ampo powder as an explosive. for crimes such asillegal fishing. The judge's basic considerations in imposing a criminal offense against the perpetrators of the crime of possession of ampo powder as explosives based on Decision Number: 488/Pid.Sus/2021/PN Tjk are aggravating matters, namely the actions of the defendant can endanger the safety of the people and themselves, while mitigating things is the first time the defendant has faced the law, admitted his actions and promised not to do it again, the defendant was polite and cooperative during the trial so that the trial ran smoothly. Criminal liability for the perpetrators of the crime of possessing ampo powder as explosives based on Decision Number: 488/Pid.Sus/2021/PN Tjk is by imprisonment for 1 (one) year and 6 (six) months and stipulates that the period of arrest and detention served by the Defendant is deducted entirely from the sentence imposed and stipulates that the Defendant remains detained. Abstrak Salah satu perkara mengenai kepemilikan bahan peledak adalah pada Putusan Nomor: 488/Pid.Sus/2021/PN Tjk yang menyatakan terdakwa Kurniawan Azhar Amran Bin M. Rosyid bersalah melakukan telah terbukti secara syah dan meyakinkan melakukan tindak pidana menguasai, membawa, mempunyai persediaan padanya atau mempunyai dalam miliknya, menyimpan, mengangkut, menyembunyikan, mempergunakan bahan peledak. Hasil penelitian menunjukkan bahwa faktor penyebab pelaku melakukan tindak pidana kepemilikan serbuk ampo sebagai bahan peledak berdasarkan Putusan Nomor: 488/Pid.Sus/2021/PN Tjk adalah faktor untuk menjaga diri atau membela diri. Selain itu serbuk ampo sebagai bahan peledak yang dihasilkan dari tindak pidana ini sangat digemari karena serbuk ampo sebagai bahan peledak ini tidak terdaftar sehingga sulit terlacak, terlebih lagi mudah digunakan oleh berbagi pihak di wilayah Indonesia, diantaranya terdapat orang yang menyalahgunakan serbuk ampo sebagai bahan peledak tersebut untuk kejahatan seperti mencari ikan secara ilegal (illegal fishing). Dasar pertimbangan Hakim dalam menjatuhkan pidana terhadap pelaku tindak pidana kepemilikan serbuk ampo sebagai bahan peledak berdasarkan Putusan Nomor: 488/Pid.Sus/2021/PN Tjk adalah hal yang memberatkan yaitu perbuatan terdakwa dapat membahayakan keselamatan orang banyak dan diri sendiri, sedangkan hal yang meringankan adalah terdakwa baru pertama kali berhadapan dengan hukum, mengakui perbuatannya serta berjanji tidak akan mengulanginya kembali, terdakwa sopan dan kooperatif selama persidangan sehingga persidangan lancar. Pertanggungjawaban pidana terhadap pelaku tindak pidana kepemilikan serbuk ampo sebagai bahan peledak berdasarkan Putusan Nomor: 488/Pid.Sus/2021/PN Tjk adalah dengan pidana penjara selama 1 (satu) tahun dan 6 (enam) bulan dan menetapkan masa penangkapan serta penahanan yang dijalani Terdakwa dikurangkan seluruhnya dari pidana yang dijatuhkan dan menetapkan Terdakwa tetap ditahan.